Thyroid medications and patient adherence: understanding prescription patterns and factors influencing treatment compliance - Poojary, Bhavya; Wilson, Merlin Maria; Jose, Riya; Sam, Sona P; George, Ann Elizabeth (Indonesian Journal of Pharmacology and Therapy, 2023)
Thyroid problems are common in India affecting around 42 million people. Early diagnosis and therapy play an important role in managing this endocrine disorder. Hypothyroidism and hyperthyroidism are the most common thyroid disorders and are treated with thyroid hormone replacement therapy and antithyroid drugs. However, medication adherence, side effects, and misunderstanding of the importance of medication lead to inconsistent intake. This study aimed to evaluate the pattern of prescribing and adherence to thyroid medication. This cross-sectional study was conducted over 6 months in a tertiary care hospital, involving 188 patients with thyroid disorders. Data was collected using a validated form and medication adherence rationing scale. The collected data, including MARS scores, were entered into Microsoft Excel and analyzed using IBM SPSS Version 25. Quantitative data were analyzed using the mean and standard deviation, while categorical data were summarized using frequencies and percentages. The Chi-square test was used to evaluate associations, with a significance level of p < 0.05. In our study, 163 participants diagnosed with hypothyroidism exhibited a notable adherence rate of 89.57%. The 25 hyperthyroid patients showed strong adherence to the recommended drugs, with those provided methimazole having the highest adherence rate (52.0%). No statistically significant connections were found when examining the variables affecting drug adherence. Levothyroxine and methimazole were the preferred medications for managing hypothyroidism and hyperthyroidism, respectively. A high adherence rate among patients indicates heightened awareness and understanding of their condition, as well as consistent adherence to the medication schedule. These findings emphasize the importance of early diagnosis, appropriate prescription patterns, and patient adherence in effectively managing thyroid disorders.